Disrupted structural connectivity and less efficient network system in patients with the treatment-naive adult attention-deficit/hyperactivity disorder - Ohnishi, Takashi; Toda, Wataru; Itagaki, Shuntaro; Sato, Aya; Matsumoto, Junya; Ito, Hiroshi; Ishii, Shiro; Miura, Itaru; Yabe, Hirooki (Frontiers in Psychiatry, 2023)
Introduction: Attention-deficit/hyperactivity disorder (ADHD) is a neuropsychiatric disorder whose primary symptoms are hyperactivity, impulsivity, and inattention. Historically, ADHD was recognized as a disease of childhood and adolescence. However, many patients are known to have persistent symptoms into adulthood. Many researchers consider the neuropathology of ADHD to be based on abnormalities in multiple parallel and intersecting pathways rather than a single anatomical area, but such alterations remain to be clarified. Methods: Using diffusion tensor imaging, we investigated differences in the global network metrics estimated by graph theory and the degree of connectivity between adjacent voxels within a white matter (WM) fascicle defined by the density of the diffusing spins (connectometry) between 19 drug-naive Japanese adult ADHD patients and 19 matched healthy controls (HCs). In adult ADHD, we examined relationships between the symptomatology of ADHD and global network metrics and WM abnormalities. Results: Compared to HCs, adult ADHD patients showed a reduced rich-club coefficient and decreased connectivity in widely distributed WMs such as corpus callosum, forceps, and cingulum bundle. Correlational analyses demonstrated the general severity of ADHD symptoms was associated with several global network metrics, such as lower global efficiency, clustering coefficient, small worldness, and longer characteristic path length. The connectometry revealed that the severity of hyperactive/impulsive symptoms was associated with overconnectivity in the corticostriatal, corticospinal, corticopontine tracts, inferior fronto-occipital fasciculus, and extreme capsule, whilst dysconnectivity in the cerebellum. The severity of inattentive symptoms was associated with dysconnectivity in the intracerebellar circuit and some other fibers. Conclusions: The results of the present study indicated that treatment-naive adult ADHD showed disrupted structural connectivity and it contributes to less efficient information transfer in the ADHD brain and pathophysiology of ADHD.